Improving Science Scores of Middle School Students with Learning Disabilities through Engineering Problem Solving Activities - Starling, A. Leyf Peirce; Lo, Ya-Yu; Rivera, Christopher J. (Journal of the American Academy of Special Education Professionals, 2015)
This study evaluated the differential effects of three different science teaching methods, namely engineering teaching kit (ETK), explicit instruction (EI), and a combination of the two methods (ETK+EI), in two sixth-grade science classrooms. Twelve students with learning disabilities (LD) and/or attention deficit hyperactivity disorder (ADHD) participated in this study. The dependent variables included students’ performance on daily quizzes covering the material taught in that day’s lesson and students’ performance on a pretest and two posttests covering the steps of the engineering problem solving process. Using a multiple probe across science units design, we demonstrated that both the ETK and EI interventions alone increased the participants’ quiz scores, with the combined method (ETK+EI) producing slightly better results in most participants. Students’ understanding of the engineering problem solving process also improved after being exposed to the ETK method. Limitations, suggestions for future research, and practical applications are discussed.